2018
DOI: 10.1080/13548506.2018.1450518
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness and adherence to the oral contraceptive pill: a cross-sectional analysis of the facets of conscientiousness

Abstract: We examine the association between a six-facet model of conscientiousness and adherence to the Oral Contraceptive Pill (OCP), to investigate if these 6 facets can account for variation in adherence to the OCP. Cross-sectional data were collected from an opportunity sample of 243 female participants who were current users of the OCP, via online survey. Data were analysed using correlation and standard regression. The 60-item Chernyshenko Conscientiousness Scale (CCS), the 10-item IPIP Conscientiousness (IPIP C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We expected that personality, particularly conscientiousness, would have a direct effect on attitudes toward social distancing and adherence to the SAH order (Eustace et al, 2018;Lima et al, 2018;Molloy et al, 2014 ); however, it did not. This may be reflective of the intensity of media coverage and widespread concern in the early days of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We expected that personality, particularly conscientiousness, would have a direct effect on attitudes toward social distancing and adherence to the SAH order (Eustace et al, 2018;Lima et al, 2018;Molloy et al, 2014 ); however, it did not. This may be reflective of the intensity of media coverage and widespread concern in the early days of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Personality traits of conscientiousness, extraversion, and neuroticism (Costa & McCrae, 1995) are likely to be relevant for understanding adherence to social distancing recommendations. For example, conscientious individuals are dutiful rules-followers and conscientiousness is predictive of health behaviors such as medication adherence (Eustace et al, 2018;Molloy et al, 2014 ) and adherence to instructions during cancer treatment (Lima et al, 2018).…”
Section: Personalitymentioning
confidence: 99%
“…While research has demonstrated that conscientiousness is related to many individual health behaviours (e.g. Eustace et al, 2018;Furnham & Cheng, 2018;Steptoe, Easterlin & Kirschbaum, 2017;Wilson et al, 2016), and a few have created summary health behaviour variables which can give an indication of a healthy lifestyle more broadly (Hampson et al, 2015;Joyner et al, 2018;Takahashi et al, 2013), we are not aware of any studies which have assessed participants' adherence to national health guidelines as a benchmark for health behaviour. Therefore, this is an important finding because it highlights the value of health behaviour guideline adherence indexes for future research.…”
Section: Discussionmentioning
confidence: 99%